PENGARUH ENVIRONMENTAL MANAGEMENT ACCOUNTING TERHADAP KINERJA PERUSAHAAN MELALUI ESG DISCLOSURE (Studi Empiris Perusahaan Sektor Energi Asia Pasifik pada Tahun 2021-2024) - Raihan Sayyid Husain; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2026)
This study aims to determine the direct effect of Environmental Management Accounting (EMA) on firm performance mediated by ESG Disclosure. This study uses Environmental Management Accounting (EMA) as the independent variable, firm performance measured by Return On Assets (ROA) and Tobin's Q proxies as the dependent variable, and ESG Disclosure as the mediating variable.The data used in this study are secondary data, with the research population comprising energy sector companies in the Asia Pacific region based on the Global Industry Classification Standard (GICS) during the 2021-2024 period. This study utilized a purposive sampling method, resulting in 49 companies that met the predetermined criteria as the research sample[cite: 2]. The data were processed and analyzed using multiple linear regression, path analysis, and the Sobel test with the SPSS version 29 software.The results of the study show that Environmental Management Accounting (EMA) has no effect on firm performance (neither ROA nor Tobin's Q). On the other hand, Environmental Management Accounting (EMA) has a positive effect on ESG Disclosure, and ESG Disclosure has a positive effect on firm performance (both ROA and Tobin's Q)[cite: 2]. This study also found that ESG Disclosure cannot mediate the relationship between Environmental Management Accounting (EMA) and firm performance (both ROA and Tobin's Q).